If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8n+11=7+4(2n-1)
We move all terms to the left:
8n+11-(7+4(2n-1))=0
We calculate terms in parentheses: -(7+4(2n-1)), so:We get rid of parentheses
7+4(2n-1)
determiningTheFunctionDomain 4(2n-1)+7
We multiply parentheses
8n-4+7
We add all the numbers together, and all the variables
8n+3
Back to the equation:
-(8n+3)
8n-8n-3+11=0
We add all the numbers together, and all the variables
8!=0
There is no solution for this equation
| 6(m+2)-2(2m+3)=36 | | X-5-2x=3(x-3)-2(x+7) | | -11/4n=32/3 | | q²-4(q×3)+27=0 | | 2b-9=6 | | X+5x=85 | | -98=-7(4+2b) | | 4(4+4x)-3=-60 | | -7w/23=7 | | 1.2x(4+5x)=3x(2x+1)-9 | | 6x-72=-8 | | 12=w/10 | | X^2+-x+3=0 | | x+10+2x=5 | | 4^{2z/3}=8^{z+2} | | 5/2–2g=5/2g–3 | | Y=1/4x+5(-1,6) | | 2(x+6)+4=-2(x+4) | | 52–2g=52g–3 | | (x+5)/4=x+8 | | 1/4k–3+5/4k–1=3/8k+2 | | Y=-3/2x+8(2/3,7) | | 72=8(m-90) | | 6(d+2)=20+2d | | 4=11x-4(0,-4) | | |(x+5)/6-1/12|=13/24 | | 2x+22=2+5(4-3x) | | 2(4x+2)=4x=12(x-1) | | 8(g-93)=48 | | (x-3)/2=3x+1 | | c/3+7.55=8.63 | | 2x(3x-1)-8=-2(4x+5) |